An Analysis of Orthopedic Surgical Services Provided to Syrian Refugees in a Health Center Away from the Syria District - Uzun Dirvar, Sevda; Dirvar, Ferdi; Çapar, Haşim; Baktır, Yusuf (Innovative Journals, 2020)
Background: The Arab Spring, a wave of demonstrations and protests that had taken place in the Arab world since December 18, 2010, had also affected Syria. The number of Syrian refugees who have migrated to Turkey is over 3.5 million. Objective: The aim of this study was to evaluate the demography, clinical features and invoice amounts of Syrian refugee patients who were operated in an orthopedic and traumatology clinic of a healthcare institution far from the Syria district region. Materials and Methods: For this purpose, 329 Syrian patients who underwent surgery in the field of orthopedics and Traumatology between June 2011 and 2018 were enrolled in the study. The records of Syrian refugees have been retrospectively examined. Results: Male applicants (76.3%) were more than females (23.7%).%). It was observed that the highest number of applications were in the field of microsurgery (21.3%), followed by trauma (20.7%) and pediatric orthopedics (14.6%), respectively. Including the non-emergency trauma patients, 90% of the patients underwent elective surgeries while 10% underwent emergency surgeries. It was determined that the average invoice amount was 4987 TL (min: 207 TL, max: 87541 TL) and the highest cost was in the field of vertebral surgery (average 19384 TL). The rate of emergency applications has shown a significant increase in 2016 and later (2016-2017-2018) compared to 2015 and before . Conclusion : The main Syrian refugees patient profile of the health centers far from the war zone is composed of elective cases and their costs. Key words: Health Services Accessibility–Hospital Costs–Orthopedic Procedures– Refugees–Syria
Keywords: Health Services Accessibility; Hospital Costs; Orthopedic Procedures; Refugees; Syria